Removing Excess Iron from Sewage and Natural Waters: Selecting Optimal Sorbent - Ludmila A. Ivanova; Irina V. Timoshchuk; Alena K. Gorelkina; Ekaterina S. Mikhaylova; Nadezhda S. Golubeva; Evgeny N. Neverov; Tamara A. Utrobina (Техника и технология пищевых производств)
Natural waters and wastewaters often contain heavy metals, e.g., iron. Iron ore mining contaminates groundwater with iron up to 30 maximal permissible concentrations (MPC) as this element gets washed out from rock and soil. Adsorption is the most effective and economically feasible method of additional purification of natural and wastewater from iron. Its efficiency depends on the type of adsorbent. The research objective was to select the most efficient sorption material to eliminate water from iron, as well as to establish the adsorption patterns for different sorbents, thus creating sustainable and effective purification. The study featured carbonaceous sorbent of the SKD-515 grade, mineral sorption materials with aluminosilicate of the AC grade, and silicate-based sorbent of the ODM-2F grade. The porous structure was studied by porometry methods while the surface image was obtained using scanning electron microscopy. Other indicators included equilibrium, kinetics, and dynamics of iron adsorption by various sorbents. The Freundlich and Langmuir equations made it possible to calculate the key adsorption parameters. The Gibbs energy values were obtained from the Langmuir equation and equaled 11.93–20.66 kJ/mol, which indicated the physical nature of the adsorption process. Under static conditions, the sorbents demonstrated a high adsorption capacity with respect to iron, depending on the structure, and could be arranged as AC > SKD-515 > ODM-2F. In SKD-515, iron adsorption occurred in micropores; in AC and ODM-2F, it took place in mesopores. The kinetics of iron extraction showed that the adsorption process was limited by external mass transfer. The research provided a new understanding of iron adsorption by materials of various structures. The conclusions were supported by scanning electron microscopy images. Initial concentration, flow velocity, and loading layer height were studied in dynamics, i.e., during continuous operation of the adsorption column. The system proved extremely effective and reached 99.0% Fe3+ extraction under the following conditions: flow rate = 1 L/min, loading column height = 0.15 m, column diameter = 0.05 m, initial concentration = 0.5 mg/L (5 MPC). The column performance was tested at an initial concentration of iron ions of 50 MPC, which simulated the wastewater treatment at industrial enterprises. This comprehensive study of iron adsorption from wastewater proved the efficiency of the mineral sorption materials with aluminosilicate of AC grade.